CHANGES IN THE PHOSPHORYLASE ENZYME ACTIVITY LEVELS IN THE TISSUES OF THE BARYTELPHUSA GUERINI (MILNE EDWARDS) DUE TO MONOCROTOPHOS STRESS - VENKATESHWARLU, M.; SUNITA, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The total phosphorylase and active phosphorylase enzyme activity in the muscle and hepatopancreas tissues of the Barytellphusa guerini considerably increased on exposure to monocrotophos pesticide, but the inactive form of phosphorylase activity not shown considerable change. The phosphorylase activity levels are restored to normal during recovery period.